2017
DOI: 10.1111/nph.14501
|View full text |Cite
|
Sign up to set email alerts
|

Cutting in the middleman: hidden substrates at the interface between proteases and plant development

Abstract: Contents Summary 916 I. Introduction 916 II. DEK1: towards identification of protease substrates 917 III. Separases: when proteolytic modules attain nonproteolytic functions 918 IV. The peculiar case of a nonredundant subtilisin 919 V. Towards a solution to the protease redundancy problem 920 VI. Matters arising and closing remarks 921 Acknowledgements 921 References 921 SUMMARY: Proteases are integral components of proteome remodelling networks that regulate turnover of proteins and expand their functional di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Furthermore, reactive oxygen signaling mediated by respiratory burst oxidase homolog (RBOH) proteins along with the transmembrane receptor kinase signaling by the extracellular peptide RALF (rapid alkalinization factor 1) can be integrated through the AHAs to generate apo pH changes (reviewed by Mangano et al ., ). In this context, it is interesting to note that an AHA has been identified among potential targets for AtMC9 (Tsiatsiani et al ., ), whereas the degradome for the Arabidopsis separase, which was reported to relate structurally to metacaspases (Liu and Moschou, ), also contain two AHAs (Liu et al ., ). These results thus indicate that AHAs could be direct targets for type‐II MCs and may hint at possible feedback interactions between the MC9 class of type‐II MCs and AHA functions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, reactive oxygen signaling mediated by respiratory burst oxidase homolog (RBOH) proteins along with the transmembrane receptor kinase signaling by the extracellular peptide RALF (rapid alkalinization factor 1) can be integrated through the AHAs to generate apo pH changes (reviewed by Mangano et al ., ). In this context, it is interesting to note that an AHA has been identified among potential targets for AtMC9 (Tsiatsiani et al ., ), whereas the degradome for the Arabidopsis separase, which was reported to relate structurally to metacaspases (Liu and Moschou, ), also contain two AHAs (Liu et al ., ). These results thus indicate that AHAs could be direct targets for type‐II MCs and may hint at possible feedback interactions between the MC9 class of type‐II MCs and AHA functions.…”
Section: Discussionmentioning
confidence: 99%
“…CRSP negatively regulates stomatal development under high CO 2 concentration by processing the EPF2 precursor [39]. This processing results to blockage of the asymmetric divisions of the MMCs [42].…”
Section: Subtilisin-like Serine Proteasesmentioning
confidence: 99%
“…In addition to Arg, other amino‐acids or modified forms also serve as primary destabilizing residues for direct recognition by E3 ligase N‐recognins (Figure A) (Varshavsky ). Physiological substrates with destabilizing residues have been identified, but in many cases biochemical components of the pathway and diversity of destabilizing residues were initially determined with artificial substrates using the ubiquitin fusion technique (Bachmair et al ) that allows the generation of a stoichiometric mixture of stable and test proteoforms (in this context polypeptides produced after proteolytic cleavage events; Liu and Moschou ) following constitutive deubiquitinase activity, whose relative stabilities can then be monitored (Bachmair et al ; Graciet et al ). Analysis of the half‐lives of artificial N‐degron pathway substrates in plants ( Arabidopsis thaliana , hereafter Arabidopsis and Nicotiana tabacum , tobacco) showed that destabilizing residue identity is conserved with higher animals, including the observation of Nt‐Cys as a destabilizing residue (Graciet et al ).…”
Section: What Are N‐degron Pathways?mentioning
confidence: 99%